2018
DOI: 10.1038/s41598-018-33762-8
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Bacillus subtilis DSM 32315 manipulates intestinal structure and microbial composition in broiler chickens

Abstract: Knowledge about the modulation of gut microbiota improves our understanding of the underlying mechanism by which probiotic treatment benefits the chickens. This study examined the effects of Bacillus subtilis DSM 32315 on intestinal structure and microbial composition in broilers. Broiler chicks were fed basal diets without or with B. subtilis supplementation (1.0 × 109 spores/kg of diet). Supplemental B. subtilis increased average body weight and average daily gain, as well as elevated villus height and villu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 63 publications
10
82
0
Order By: Relevance
“…In addition, post-weaning diarrhea is also associated with increased gut permeability due to the disturbed tight junction protein expression in the small intestine [34]. In the current study, supplementation of Bacillus subtilis DSM 32540 increased ileal villi height and duodenal crypt depth compared with pigs in the control group on d 21 PI, which was also reported in other studies where the same Bacillus subtilis strain was used in pigs and chickens under normal housing conditions [45,46]. The villus is populated by differentiated enterocytes that have distinctive absorptive and secretary functions, while the crypt is populated by stem cells that are rapidly proliferating and differentiating [47].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, post-weaning diarrhea is also associated with increased gut permeability due to the disturbed tight junction protein expression in the small intestine [34]. In the current study, supplementation of Bacillus subtilis DSM 32540 increased ileal villi height and duodenal crypt depth compared with pigs in the control group on d 21 PI, which was also reported in other studies where the same Bacillus subtilis strain was used in pigs and chickens under normal housing conditions [45,46]. The villus is populated by differentiated enterocytes that have distinctive absorptive and secretary functions, while the crypt is populated by stem cells that are rapidly proliferating and differentiating [47].…”
Section: Discussionsupporting
confidence: 87%
“…It is reported that B. subtilis vegetative cells are present in the gastrointestinal tracts of birds as normal residents (75). However, a decrease in the relative abundance of Bacilli in the probiotic-fed groups compared to the control, which was observed in the developer and layer phases, may suggest a feedback of lessened potential pathogens after its supplementation (72,76), possibly creating a conducive environment in modifying the structure of the cecal microbiome. On the other hand, probiotics containing dead organisms have also been shown to express beneficial effects (77,78), such as by inducing specific immune responses based on the ability of immune cells to recognize individual bacterial cell structural components (79).…”
Section: Discussionmentioning
confidence: 93%
“…and reduced Escherichia coli levels in the intestinal contents of DFMsupplemented birds, compared with controls. Increased growth performance, nutrient utilization, and intestinal villus/crypt morphometry, as well as altered composition of gut microbiota, also were observed in chickens orally administered with Bacillus DFMs, compared with controls (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 94%